CD4+CD28– T-cell expansions in ANCA-associated vasculitis and association with arterial stiffness: baseline data from a randomised controlled trial. (26th February 2015) - Chanouzas, Dimitrios; Dyall, Lovesh; Dale, Jessica; Moss, Paul; Morgan, Matthew; Harper, Lorraine
Abstract: Background: Cardiovascular risk is increased in the anti-neutrophil cytoplasm antibody (ANCA)-associated vasculitides (AAV). CD4+CD28– T cells are expanded in patients with AAV who are seropositive for cytomegalovirus (CMV), and are associated with increased mortality. CMV seropositivity in other conditions is associated with arterial stiffness, a marker of cardiovascular risk. We assessed whether CD4+CD28– T cells in CMV seropositive patients with AAV are associated with arterial stiffness and whether treatment with valaciclovir reduces this cell population. Methods: In this open-label phase 2 trial, patients were randomised (1:1) by computer to valaciclovir (8 g daily) or no additional treatment for 6 months. Primary outcome was proportion of patients with CMV reactivation. Arterial stiffness (carotid to femoral pulse wave velocity [PWV]) was measured and peripheral blood CD4+CD28– T cells analysed by flow cytometry at baseline and 6 months. CD4+CD28– T-cell interferon γ (IFNγ) secretion was stimulated with CMV lysate. Data are presented as median (IQR). Between-group differences were tested by Mann-Whitney U test and correlations by Spearman's rank. Analysis was by intention to treat. This trial is registered with ClinicalTrials.gov, number NCT01633476 . Findings: Baseline data are presented from the first 28 patients enrolled, with 6 months' follow-up completed in five treatment and six control patients. More CD4+CD28– than CD4+CD28+ T cells expressed T-bet (83·5% [47·5–89·9] vs 12·9 [4·7–22·2], p<0·0001) and secreted IFNγ after stimulation (14·3% [8·4–26·0] vs 0·8 [0·2–1·3], p<0·0001). CX3CR1, a cell surface marker whose expression is associated with endothelial dysfunction, was only expressed on CD4+CD28– T cells. The proportion of CD4+CD28– T cells correlated with PWV ( r =0·408, p=0·035). At 6 months, reduction in proportion of CD4+CD28– T cells was greater in the treatment than in the control group (−1·8% [–5·2 to −0·6] vs 0·5 [–0·8 to 2·5], p=0·044). Interpretation: These preliminary results suggest that CD4+CD28– T cells in AAV are proinflammatory cells with high expression of the fractalkine receptor CX3CR1 that has been implicated in endothelial dysfunction. This cell population is associated with arterial stiffness, and its expansion is attenuated with valaciclovir treatment. This research has important implications, because cardiovascular disease is a major cause of mortality in AAV. Funding: Wellcome Trust, Vasculitis UK.